It's about time: The role of temporal variability in improving assessment of executive functioning. Issue 4 (18th May 2020) - McKinney, Ty L.; Euler, Matthew J.; Butner, Jonathan E.
Abstract: Objective: Executive Functioning (EF) is a group of cognitive abilities related to one's capacity to engage in and maintain goal-oriented behaviours and is one of the most important constructs in neuropsychology. Although EF has been repeatedly linked to response variability and is known to be impacted by various moderators (e.g., stress, sleep, etc.), in practice, EF is typically considered a stable trait. This article seeks to extend this conventional view, by highlighting the additional role of within-subject temporal variability in manifestations of EF and the potential of emerging technologies to better incorporate these dynamics into neuropsychological assessment. Method: Narrative review. Key developmental and dynamical systems concepts for operationalizing different forms of temporal patterns are reviewed. The applicability of these concepts to neuropsychology is then illustrated via specific clinical examples. Ecological Momentary Assessment (EMA) is posited as a potentially critical methodology for capturing temporal patterns in EF, particularly in combination with advances in smartphone technology. The budding literature on cognitive assessment using EMA is reviewed, concluding with a discussion of the challenges to overcome and benefits that could be realized by adopting these methods and technology for clinical use. Conclusions: The conceptualization and assessment of EF can be improved through increased attention to within-subject patterns of temporal variability. Recent technological innovations can facilitate advances in neuropsychological assessment, particularly in our ability to understand and measure the factors that promote and impede EF in daily life.